Effects of internal stress concentrations in plantar soft-tissue—A preliminary three-dimensional finite element analysis - Chen, Wen-Ming; Lee, Taeyong; Lee, Peter Vee-Sin; Lee, Jin Woo; Lee, Sung-Jae (Medical engineering & physics, 2010)
It has been hypothesized that diabetic foot ulceration might be internally initiated. This study established a three-dimensional and nonlinear finite element model of a human foot complex with comprehensive skeletal and soft-tissue components. The model was validated by experimental data of subject-specific barefoot plantar pressure measurements. The feasibility of the model to predict the 3D, internal, plantar soft-tissue deformation and stress was evaluated. The preliminary results indicate that large von Mises stress occurs where plantar soft-tissue contacts with geometrically irregular bony structures, thus internal stress distribution within the plantar soft-tissue was dramatically influenced by bony prominences due to stress concentration. At the forefoot part, an average stress magnification factor of 3.01 was quantified. The lateral sesamoid bone associated to the 1st MTH showed the largest effect of stress concentration. The modeling approach presented provides a possible way to explore the complexity of the mechanical environment inside the plantar soft-tissue.